Antiulcerogenic, Anti-Secretory and Cytoprotective Effects of Piper Cubeba (L.) on Experimental Ulcer Models in Rat - AlSaid, Mansour; Al-Mofleh, Ibrahim; Raish, Mohammad; Al-Sobaihani, Mohammed; Al-Yahya, Mohammed; Rafatullah, Syed (International Journal of Biotechnology for Wellness Industries, 2013)
This paper evaluated anti-gastric ulcer and anti-secretory effects of a popular spice Piper cubeba L, (Family: Piperaceae) in rats. The gastric ulcer protective potential of an aqueous suspension of Piper cubeba (PCS) was evaluated against different acute gastric ulcer models in rats induced by pyloric ligation (Shay), hypothermic restraint stress, indomethacin and by necrotizing agents (80% ethanol, 0.2 M NaOH and 25% NaCl) induced gastric mucosal injury. Piper cubeba aqueous suspension (PCS) at the doses 250 and 500 mg/kg body weight administered orally (intraperitoneally in Shay rat model) showed a dose-dependent ulcer protective effects in all the above models. Besides, the PCS offered protection against ethanol-induced depletion of gastric wall mucus (GWM); replenished the reduced non-protein sulfhydryls (NP‑SH) concentration and significantly replenished malondialdehyde (MDA) contents in the gastric tissue. Ethanol induced histopathological lesions of the stomach wall characterized by mucosal hemorrhages and edema was reversed by Piper cubeba aqueous suspension treatment. Pretreatment of rats with Piper cubeba provided significant protection of gastric mucosa through its antioxidant capacity and/or by attenuating the offensive and by enhancing the defensive factor.